Pertanggungjawaban Pidana Korporasi dalam Kecelakaan Kendaraan Otonom: Analisis Kedudukan Agen Pemegang Merek sebagai Distributor - Ivan Rachmawan; Frans Simangunsong (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of autonomous vehicles driven by Artificial Intelligence has fundamentally transformed the transportation system from a human-driven model to an AI-driven operational framework. This transformation has created new legal challenges concerning criminal liability for traffic accidents, as driving decisions are no longer exclusively controlled by human drivers. In Indonesia, the legal framework governing autonomous vehicles remains inadequate, particularly regarding the allocation of legal responsibility among parties involved in the autonomous vehicle ecosystem, including the position of the Authorized Brand Holder (Agen Pemegang Merek/APM) as the official distributor. This study aims to analyze the legal status of the APM as a corporation that may be held criminally liable within the autonomous vehicle ecosystem and to examine the mechanism of corporate criminal liability applicable to the APM in autonomous vehicle accidents. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. The study relies on primary, secondary, and tertiary legal materials, which are analyzed qualitatively through descriptive-analytical methods. The findings demonstrate that the APM should no longer be viewed merely as a vehicle distributor but as a corporation exercising legal control over vehicle safety through responsibilities such as software updates, product recalls, after-sales services, and compliance with safety standards. These responsibilities constitute the legal basis for attributing corporate criminal liability when the APM's negligence is causally linked to an autonomous vehicle accident. Furthermore, the mechanism for imposing criminal liability requires comprehensive proof supported by electronic evidence, digital records, and expert testimony.